The children of La Hille : eluding Nazi capture during World War II - Reed, Walter W., 1924- (Modern Jewish history., 2015)
Following the horrors of Kristallnacht in November of 1938, a courageous group of Belgian women organized a desperate and highly dangerous rescue mission to usher nearly 1,000 children out of Germany and Austria. Ninety-three were placed on a freight train, traveling through the night into the relative safety of Vichy France. Ranging in age from five to sixteen years, the children and their protectors spent a harsh winter in an abandoned barn with little food before eventually finding shelter in the isolated Château de la Hille in southern France. Remarkably, all but eleven of the original ninety-three children survived the war. As one of the La Hille children, Reed recalls with poignant detail traveling from lice-infested, abandoned convents to stately homes in the foothills of the Pyrenees, always scrambling to keep one step ahead of the Nazis.